ANALISIS PELAKSANAAN TUGAS KEPALA DESA DALAM MEMBINA KEHIDUPAN MASYARAKAT DESA DI DESA PULAU PADANG KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Taufiq, Fadlul; Syafhendry, Syafhendry (UIR PRESS, 2016)
This research is a descriptive study conducted survey using quantitative methods. The purpose of this study is to investigate the implementation and inhibiting factors in the Village Head Fostering rural community life. The population in this study is the village secretary, Head of Government Affairs, Head of Development, Head of Public Affairs, Chief of Hamlet, Village Consultative Body, Neighborhood, Rukun Warga, and the heads of families using census techniques. Meanwhile, Head of Family using purposive sampling (purposive sampling). The technique of collecting data through interviews, questionnaires and observations. This research uses descriptive quantitative technique, the research done by describing based on existing conditions in the field of research. Furthermore, to add to the collection of data, the authors also use Based on the research results can be concluded Analysis Duties Village Head in Foster Village Community Life is Less Done. The factors inhibiting the implementation of the execution of tasks of the village chief is still the lack of supervision of the Head of the village in terms of fostering community life, number of community activities that are positive, still less to the attention of the Village Head and kurangny active role of communities and community organizations in coordination with the head Village. So the task of the village head has not been fully implemented.